Finite Element Simulation and Low‐Temperature Spark Plasma Sintering for Ti–Zr–Ni Alloy. Issue 5 (29th June 2022) - Luo, Shuyi; Luo, Junting; Liu, Yongkang; Li, Zhenlun; Wang, Guofeng
Abstract : Herein, titanium (Ti) and zirconium (Zr) metal powders are used as starting powders and GH4169 superalloy powder is used as a sintering aid. Spark plasma sintering process is used to prepare Ti–Zr–nickel (Ni) alloy with the fine and uniform grain size of α and β phases mixed under low‐temperature conditions of 1273, 1373, and 1573 K. The thermal–mechanical–electric three‐field coupling simulation of the sintering process of alloy powder is conducted on the basis of the voltage and current data of the discharge sintering test. Results show that experimental and simulation temperatures are consistent and extension of holding time helps improve the uniformity of temperature and relative density. In the axial direction, the temperature and relative density gradually decrease from the upper surface to the lower surface of the sample. In the radial direction, the temperature gradually decreases from the center to the edge of the sample, and the relative density of the upper surface of the sample gradually decreases from the center to the edge, with an opposite change in the lower surface. The relative density of the central layer is stable and uniformity is optimal. Abstract : Spark plasma sintering process is used to prepare Ti–Zr–Ni alloy of α and β phases mixed under low‐temperature conditions of 1273, 1373, and 1573 K. The thermal–mechanical–electric three‐field coupling simulation of the sintering process of alloy powder is conducted on the basis of the voltage and current data of the sintering test.